A recepção e circulação da teoria clausewitziana no Exército brasileiro (1889-1959) - Ferezin, Carla Cristina Wrbieta (2017)
Clausewitz is an icon among those who are engaged in research war strategy, considered one of the main makers of modern military thinking. His ideas have been read and repeatedly quoted at least since 1871, especially in the military means. However, there is a hiatus in the literature regarding the reading of this author among the Brazilian military. In this sense, the aim of this research is to understand the reception and circulation of Clausewitz conceptions in Brazil, mainly, but not exclusively, between soldiers belonging to the Brazilian Army between 1889 and 1959, such period that the prosecutors have been searching for professionalization, modernization and restructuring of the Brazilian Army, under instructions from Germany, France and the United States of America. We hypothesize that Brazilian readers may have disregarded the context of production and cast their own perceptions and desires of their context on Clausewitz's work, On War. In this direction, we selected a temporal clipping that allowed us to investigate if the war conjunctures (internal and external) and the process of military professionalization that impacted the Clausewitz reading in Brazil. The research process on the reception and circulation of Clausewitz in Brazil was made through the analysis of a series of articles published in a military journal, A Defesa Nacional, and in several contemporary periodicals that grant sessions to discuss military topics. From a qualitative perspective, based on methods of bibliographical research, documentary research and content analysis methodology, we reach the understanding that the reception and circulation of the Clausewitzian theory in Brazil between the years 1889 to 1959 is marked by misunderstandings (disregard of the context of production, insertion of perceptions and problematics proper to the context of the reader, instrumentalized readings and partial translations) proper to the great classics. Moreover, the context of wars greatly impacted Clausewitz's readings in Brazil, with several mentions to the Prussian general as the theoretician of the immoral war, bloodless and without limits, however, a less negative reading also had space, especially those that dealt with the relationship between war and politics. The process of professionalization was also found to be relevant in Clausewitz's reception in Brazil, since it probably enabled the first partial translation into the Portuguese language of excerpts from On War, in the years 1931 and 1932, in the magazine A Defesa Nacional, at the time of the French Military Mission in the Brazilian Army.